(untitled) (Annals of Medical Research, 2021)
Aim: Shock wave lithotripsy (SWL) is a well-known technique used in the treatment of kidney stones since the early eighties. For successful SWL, accurate visualization of the shock waves is performed by ultrasound (US) or fluoroscope (FS) to fully focus the shock waves on the stone. In this study, we aimed to investigate the effect of US and FS methods used for focusing on stone in SWL treatment of renal stones in pediatric patients on side effect and treatment success.Material and Methods: Between January 2008 and January 2018, 495 children under 16 years of age who were treated with SWL using ultrasonic and fluoroscopic focusing were included in the study. Patients with fluoroscopic focus were classified as Group 1 and patients with ultrasonic focus were classified as Group 2. Demographic data, SWL parameters and success rates of the two groups were compared..Results: There was no significant difference between the demographic data, stone localization and stone sizes of the groups. SWL success rate was 90.5% in group 1 and 92.3% in group 2. There was no significant difference between the two groups in terms of success (p = 0.474). Complication rates were 0.2% (1 patient) and 0.4% (2 patients) in groups 1 and 2, respectively, and there was no statistically significant difference (p = 0.495). With increasing clinical experience, ultrasonic focusing rates have increased and fluoroscopic focusing rates have decreased over the years. Conclusion: In the pediatric age group, we recommend the use of ultrasonic focusing with the additional advantage of avoiding radiation, avoiding the fluoroscopic focusing method using ionized radiation for SWL. We believe that randomized prospective studies will be more informative and support our study.